2021
DOI: 10.1088/1757-899x/1090/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Smart System for School Children Tracking

Abstract: What the world is seeing about the deterioration of public safety in various cities and the increase in the rate of crimes against children makes parents constantly worry about their children when they go to school and until they return from it. To dispel these fears, the idea emerges to create an application that allows parents to know the whereabouts of their children and notify them with a message if the children exceed the area specified for them. In this application, the process of discovering the child’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In [15][16][17][18], authors emphasized that e-learning is one of the comfortable means of education for learners as it provides educational content in any place and time and this is not possible to fully achieve it in the traditional study style in the classroom. In [19][20][21], they emphasized that the learner can bypass the state of boredom in e-learning and focus on important things, unlike traditional education in the classroom where everyone is forced to focus at the same time. While it was found that e-learning is characterized by flexibility and the ability to cover its expenses in a possible way for learners through the study conducted by [22,23].…”
Section: Previous Studiesmentioning
confidence: 99%
“…In [15][16][17][18], authors emphasized that e-learning is one of the comfortable means of education for learners as it provides educational content in any place and time and this is not possible to fully achieve it in the traditional study style in the classroom. In [19][20][21], they emphasized that the learner can bypass the state of boredom in e-learning and focus on important things, unlike traditional education in the classroom where everyone is forced to focus at the same time. While it was found that e-learning is characterized by flexibility and the ability to cover its expenses in a possible way for learners through the study conducted by [22,23].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Ensuring that digital skills keep pace with the advancement of technology is extremely difficult given the dynamic nature of information and communication technology, which is reflected in the rapid development of networks, service delivery methods, and speed rates of technology and devices. Today, multiple services are provided through smart devices using converged networks to obtain smart education and learning [19][20][21]. So, via the digital transformation, ushered in by the Internet of Things, artificial intelligence and big data analysis, has begun to bring innovation to learning methodologies and tools through "smart learning" practices, which the integration of smart devices and smart technologies provides a powerful way to enhance and extend the learning experience [22].…”
Section: Introductionmentioning
confidence: 99%